Triptolide alleviates psoriasis through inhibiting the Wnt5a/β-Catenin signaling pathway - Eryang Chen; Lei Wang; Lei Wang; Qu Wang; Qu Wang; Yan Cai; Yaning Dou; Hongyan Qu; Hongyan Qu; Junyi Zhu; Haiyang Zhao; Suqing Zheng; et al. (Frontiers in Pharmacology)
BackgroundPsoriasis, an immune-mediated chronic inflammatory skin disease, is characterized by keratinocyte proliferation and inflammatory cell infiltration. T ripterygium wilfordii is a potential treatment option for psoriasis, and triptolide (TP) is one of its active components. TP may possess the potential to treat psoriasis; however, its mechanism of action remains unknown.ObjectiveThe research aims to explore the therapeutic effect of TP on psoriasis and elucidate its potential targets.MethodsThe imiquimod-induced psoriasis-like lesion mouse model was used to identify the mechanism underlying the therapeutic effect of TP.RNA-seq strategy was utilized to forecast the targets and mechanisms of TP in the context of psoriasis.Finally, we verify the effect of TP in the IL-17A-induced keratinocyte hyperproliferation and inflammation model.ResultsTP reduced epidermal hyperplasia as well as psoriasis area and severity index scoring. Moreover, treatment with TP inhibited IMQ-induced splenomegaly and T-helper 17 cell differentiation in the psoriatic mice. Additionally, the treatment reduced the serum levels of pro-inflammatory cytokines such as interleukin (IL)-17A, IL-22, IL-23, IL-6, and tumor necrosis factor-α in the mice. The sequencing of RNA obtained from skin lesions of the psoriatic mice indicated that treatment with TP significantly downregulated Wnt5a RNA levels. Moreover, the Wnt5a/β-catenin pathway upregulated by IMQ was downregulated by treatment with TP. Additionally, IL-17A induced and upregulated Wnt5A and β-catenin mRNA expression, and TP inhibited this upregulated expression in HaCaT cells. Furthermore, TP inhibited proliferation, promoted apoptosis, and arrested the cell cycle in the IL-17A-induced keratinocyte hyperproliferation and inflammation model, thereby exhibiting its anti-inflammatory properties.ConclusionTP alleviated psoriasis in mice by exerting anti-inflammatory effects and inhibited keratinocyte proliferation, which was partly achieved by regulating the Wnt5a/β-catenin signaling pathway.